2009
DOI: 10.1007/s00330-009-1575-3
|View full text |Cite
|
Sign up to set email alerts
|

Bowel preparation in CT colonography: electrolyte and renal function disturbances in the frail and elderly patient

Abstract: In our group CTC with SPS-MC was safe and effective; however, we advise an alternate preparation be considered in patients with decreased renal function due to decreased magnesium clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…The respective summary of product characteristics for each of the individual magnesium-based preparations advocates the use of alternative preparations in patients with ‘severely reduced renal function’. In a recent study of 72 older patients with a mean estimated GFR of 60.8 ml/min per 1.73 m 2 and receiving sodium picosulphate with magnesium citrate (Picolax) before CT colonoscopy, serum magnesium levels were measured before and after the administration of Picolax in 14 patients 26. Although without clinical sequelae in this study, three patients experienced an increase in serum magnesium in excess of 0.25 mmol/l.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The respective summary of product characteristics for each of the individual magnesium-based preparations advocates the use of alternative preparations in patients with ‘severely reduced renal function’. In a recent study of 72 older patients with a mean estimated GFR of 60.8 ml/min per 1.73 m 2 and receiving sodium picosulphate with magnesium citrate (Picolax) before CT colonoscopy, serum magnesium levels were measured before and after the administration of Picolax in 14 patients 26. Although without clinical sequelae in this study, three patients experienced an increase in serum magnesium in excess of 0.25 mmol/l.…”
Section: Introductionmentioning
confidence: 80%
“…This risk is likely to be greatest with sodium phosphate preparations, but also exists with sodium picosulphate (although a recent study of 72 patients receiving Picolax before CT colonoscopy revealed no significant changes in estimated glomerular filtration rate (GFR)26); the risk of hypovolaemia is least with polyethylene glycol preparations.…”
Section: Introductionmentioning
confidence: 99%
“…In one small prospective study (20 healthy volunteers aged < 65 years) investigators found a disturbance of serum magnesium, whereas sodium, phosphate as well as renal parameters stayed within the normal ranges . In a retrospective study on 72 elderly patients of which 13 suffered from chronic kidney failure, no disturbance of sodium, potassium, or renal parameters were found after undergoing colon cleansing with PMC for computed tomography (CT) colonography . Another small prospective study comparing PEG and PMC in 65 patients showed no relevant electrolyte or osmolality shifts .…”
Section: Discussionmentioning
confidence: 99%
“…Commonly documented side effects include abdominal discomfort and nausea [17][18][19]. Potentially serious adverse events are rare and include vasovagal reactions, electrolyte disturbances, angina and perforation [18,20]. The reported potentially serious adverse event and overall perforation rates are 0.08% and 0.05% respectively [18].…”
Section: Discussionmentioning
confidence: 99%